PEMILIHAN METODE PERONTOKAN PADI DENGAN MENGGUNAKAN SISTEM PAKAR DI DESA SRIMARTANI, PIYUNGAN, BANTUL - , HUTAMI RAHAYU, Prof. Dr. Ir. Lilik Sutiarso, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research studied about the selection method of threshing paddy with expert system. The research conducted at Srimartani Village, Piyungan, Bantul in April until September. Srimartani Village has three threshing paddy methods, among others threshing with gebot, pedal thresher and power thresher. Data obtained from the field, sources and references processed using expert system program. Threshing paddy expert system program is also used to calculate the time and cost required to perform threshing paddy by area planted. The results of research showed that the most appropriate method of doing threshing paddy is to use the power thresher. The greater the amount of materials and land area, the greater the advantage compared to the use of power thresher threshing with pedal threshers and gebot. By using expert system threshing paddy, farmers can also compare the cost and required, and the amount of grain loss resulting from each method of threshing.